Mediation, a Form of Alternative Individual Labour Dispute Resolution - Korpič - Horvat, Etelka (Anali PAZU, 2022)
In the present article the author discusses an alternative dispute resolution of individual labour disputes by means of mediation. Mediation is one of the methods of the dispute resolution outside courts. The author outlines legal bases which are relevant for mediation at national and international levels. She particularly addresses the question concerning the admissible disposing of the parties, i.e. an employee and employer, with reference to reaching agreements on the resolution of the disputable relation. The author underlines that this is a basic question when implementing mediation proceedings with reference to the resolution of individual labour disputes, as such concerns regulating relations which are particularly sensitive because of the fact that employees are dependent on and subordinate to employers.